Narasi Kehormatan (Siri’) dalam Perkara Pembunuhan terhadap Perempuan di Sulawesi Selatan - Zul Khaidir Kadir; Nur Fadhilah Mappaselleng; Nadiah Khaeriah Kadir (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
This article examines how Indonesia’s criminal law system and judicial practice allow narratives of honour (siri’) to enter the adjudication of homicide cases involving women, and assesses the consequences for the protection of the right to life and the position of victims within criminal proceedings. The study employs a normative legal method with doctrinal and jurisprudential approaches. Primary legal materials consist of Law No. 1 of 2023 on the Criminal Code, particularly Article 458(1) and (2) on homicide and Articles 31–44 on justifying and excusing grounds, analysed alongside a corpus of court decisions from South Sulawesi. The analysis shows that siri’ operates as a causal premise in the construction of facts, primarily through the language of shame and commands to restore family honour, allowing judicial reasoning to shift from the victim’s rights to the reputational interests of the perpetrator’s family. Although the new Criminal Code establishes homicide as an unlawful deprivation of life and provides for aggravated punishment when the victim is a close family member, the discretionary space within sentencing guidelines enables honour-based motives to function as mitigating considerations, despite siri’ falling outside the closed categories of justifications and excuses. At the same time, evidentiary practices centred on chronology, perpetrator communication, and socially legitimised forgiveness narrow the space for victims as rights-bearing subjects, increasing the risk of silencing at the stages of reporting, examination, and sentencing.